2017
DOI: 10.1155/2017/2103190
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Delays Prometaphase/Metaphase of the First Cleavage in Mouse Zygotes via the MAD2L1‐Mediated Spindle Assembly Checkpoint

Abstract: In zygotes, DNA damage delays the first cleavage to enable repair. Our previous study found that 0.03 mM hydrogen peroxide (H2O2) was the minimum concentration required for induction of oxidative DNA damage in mouse zygotes and that this represented the most similar situation to the clinical phenomenon. In this study, we quantified the cleavage rates of cells in blastocysts at different developmental stages, followed by immunofluorescence to detect activation of γ-H2A histone family member X (a marker of DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…Regarding the blastocyst formation rate, inhibition of AMPK activity with Compound C led to a 36.12% reduction compared to the control group (p < 0.001) and a 17.92% reduction compared to the H 2 O 2 -treated group (p < 0.05), inhibition of AMPK activity with SBI-0206965 led to a 50.72% reduction compared to the control group (p < 0.001) and a 32.66% reduction compared to the H 2 O 2 -treated group (p < 0.001). In addition, consistently with our previous findings (Qian et al, 2016;Wu et al, 2017), the blastocyst formation rate in the H 2 O 2 -treated group was 18.06% lower than that of the control group (p < 0.05), while we observed no statistical differences in the 2-and 4-cell embryo formation rate between the control and H 2 O 2 -treated groups (Figures 7A,B).…”
Section: Inhibition Of Ampk Activity Decreased the Formation Rate Of supporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the blastocyst formation rate, inhibition of AMPK activity with Compound C led to a 36.12% reduction compared to the control group (p < 0.001) and a 17.92% reduction compared to the H 2 O 2 -treated group (p < 0.05), inhibition of AMPK activity with SBI-0206965 led to a 50.72% reduction compared to the control group (p < 0.001) and a 32.66% reduction compared to the H 2 O 2 -treated group (p < 0.001). In addition, consistently with our previous findings (Qian et al, 2016;Wu et al, 2017), the blastocyst formation rate in the H 2 O 2 -treated group was 18.06% lower than that of the control group (p < 0.05), while we observed no statistical differences in the 2-and 4-cell embryo formation rate between the control and H 2 O 2 -treated groups (Figures 7A,B).…”
Section: Inhibition Of Ampk Activity Decreased the Formation Rate Of supporting
confidence: 92%
“…Our previous results also showed that 0.03 mM H 2 O 2 induced DNA damage and caused a G2/M delay in mouse zygotes. Moreover, the delay occurred during the M phase due to the activation of the spindle assembly checkpoint (Zhang et al, 2016;Wu et al, 2017). However, these results did not confirm the existence of G2 arrest in zygotes subjected to oxidative stress, which is the typical mark of activation of the G2/M checkpoint.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…MAD2L1, a crucial component of the SAC complex, ensures chromosomal stability by regulating Aurora B (Shandilya et al, 2016 ). In a previous study, we first confirmed that ROS can arrest IVF-obtained mouse embryos in prophase/metaphase at the first mitotic cleavage through MAD2L1-mediated SAC activation (Wu et al, 2017 ). We then illustrated that SAC and DDR assist in repairing sex chromosome aneuploidy through the MAD2-mediated pathway (Huang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 54%
“…Only Aurora B overexpression (not Aurora C overexpression) can rescue chromosome alignment defects (Shuda et al, 2009 ). Aurora B has been reported to potentiate Mps1 (also known as TTK) activation to quickly establish the mitotic checkpoint (Saurin et al, 2011 ); moreover, our previous findings have shown that mitotic arrest deficient 2 like 1 (MAD2L1; also referred to as MAD2) recruitment to kinetochores by TTK occurs at the onset of oxidative damage in embryos during SAC activation (Wu et al, 2017 ). In addition, MAD2 prevents chromosome segregation defects and maintains chromosome stability through modulation of the mitotic functions of Aurora B (Shandilya et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%